CONGENITAL AFIBRINOGENEMIA IN A NEWBORN - Ozay, Mustafa; Kara, Mustafa; Keskin, Zuhal (Sanamed, 2022)
Introduction: Congenital afibrinogenemia is a rare coagulation disorder characterized by a deficiency in the fibrinogen molecule. Fibrinogen is a hexameric glycoprotein consisting of a polypeptide chain encoded by FGB, FGA, and FGG and is required for normal hemostasis. Changes in FGA, FGB, and FGG may affect fibrinogen at different levels. As a result of these changes, fibrinogen cannot be detected in the blood. Clinical manifestations of such changes range from asymptomatic to life-threatening bleeding or thromboembolic events. Since it is an autosomal recessive disease, the risk is higher in children whose parents are related. Therefore, the disease is more common in regions where consanguineous marriage rates are high. Diagnosis is made by laboratory tests that show the absence of fibrinogen. These patients need to be treated with fibrinogen replacement therapy.Case presentation: This study reports the case of a newborn with congenital afibrinogenemia. The baby born from a first-degree consanguineous marriage was referred to our hospital due to bleeding and ecchymosis, and afibrinogenemia was diagnosed after coagulation tests were performed. Blood samples of the patient and his parents were sent to the Genetic Diseases Diagnosis Center for a genetic diagnosis of afibrinogenemia. A new homozygous mutation of FGB exon 7: c.1220c>t (p.t407 m) (p.thr407 met) was identified in the patient. The patients' parents were heterozygous for the same mutation.  Prophylaxis was not recommended for our patient who was asymptomatic in the follow-up.Conclusions: We present the case of a hemorrhagic neonatal patient diagnosed with congenital afibrinogenemia and emphasize that fibrinogen testing should be included in the evaluation of such patients. Furthermore, congenital fibrinogen disorders may be more severe when caused due to unknown specific mutation genes. Therefore, a more center-involved genetic analysis is required to identify undiagnosed fibrinogen and fibrinogen mutations.
Keywords: Congenital afibrinogenemia; Fibrinogen Beta Chain; Newborn